Challenging Biblical boundaries: Jeanette Winterson's postmodern feminist subversion of Biblical discourse in Oranges are not the only fruit (1985) and Boating for beginners (1985) - Erasmus, Shirley (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 2018)
This thesis investigates the subversion of Biblical discourse in Jeanette Winterson's first two novels, Oranges are Not the Only Fruit and Boating for Beginners. By rewriting Biblical stories Winterson challenges traditional Western religious discourses and their rules for heteronormative social and sexual behaviours and desires. Winterson's texts respond to the patriarchal nature of socially pervasive texts, such as the Bible, by encouraging her readers to regard these texts with suspicion, thus highlighting what can be seen as a 'postmodern concern' with the notion of 'truth'. Chapter One of this thesis comprises a discussion of Biblical boundaries. These boundaries, I argue, are a process of historical oppression which serves to subjugate and control women, a practice inherent in the Bible and modern society. The Biblical boundaries within which women are expected to live, are carefully portrayed in Oranges and then comically and blasphemously mocked in Boating. Chapter One also argues that Winterson's sexuality plays an important role in the understanding of her texts, despite her desire for her sexuality to remain 'outside' her writing. Chapter Two of this thesis, examines the mix of fact and fiction in Oranges, in order to create a new genre: fictional memoir. The chapter introduces the concept of the 'autobiographical pact' and the textual agreement which Winterson creates with her readers. In this chapter, I examine Winterson's powerful subversion of Biblical discourse, through her narration of Jeanette's 'coming out' within a Biblical framework. Chapter Three of this thesis examines Winterson's second book, Boating, and the serious elements of this comic book. This chapter studies the various postmodern narrative techniques used in Boating in order to subvert Biblical and historical discourse. Chapter Three highlights Winterson's postmodern concern with the construction of history as 'truth'. Finally, Chapter Four compares Oranges and Boating, showing the texts as differing, yet equally relevant textual counterparts. This chapter examines the anti-feminine characters in both texts and Winterson's ability to align her reader with a feminist or lesbian viewpoint. This thesis argues that Winterson's first two texts deliberately challenge Biblical discourse in favour of a postmodern feminist viewpoint.
Keywords: Winterson, Jeanette, 1959- -- Criticism and interpretation; Bible -- Feminist criticism; Bible -- Criticism, interpretation, etc; Postmodernism -- Religious aspects; Winterson, Jeanette, 1959- -- Oranges are not the only fruit; Winterson, Jeanette, 1959- -- Boating for beginners; Patriarchy in literature; Sex discrimination in literature